BENEFIT PROGRAM LOYALITAS DALAM RETAIL ONLINE - PERLITA, LIVIANI (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Many online retailers on the internet requires each retailer to have a loyalty program. Benefits this program for retailer and customer are they can build a long relationship. This program is undertaken to improve customer loyalty in the long-term. But needed adequate planning to choose the type of loyalty program to be conducted so it looks attractive for customers and they prefer to choose this retail than others.Loyalty program is one of the types of programs that could be considered by online retailers to enhance their long-term customer loyalty. There are various benefits that can be obtained with a customer loyalty program like: social benefit, confidence benefit, ekonomic benefit, dan treatment benefit.